Pengaruh Audit Delay, Fee Audit, dan Financial Distress Terhadap Kualitas Audit - Elsa Fadia Rahayu; Rananda Septanta (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze and examine the effect of audit delay, audit fee, and financial distress on audit quality. The research uses a quantitative approach with logistic regression analysis. The data were obtained from the financial reports of consumer cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2024. The sample consists of 13 companies with a total of 78 observations. The results show that partially, audit delay and financial distress do not have a significant effect on audit quality. However, audit fee has a significant effect on audit quality. Simultaneously, audit delay, audit fee, and financial distress have a significant effect on audit quality. These findings indicate that while not all variables are individually significant, their combined effect significantly influences audit quality).